Speleological and karst glossary of Florida and the Caribbean - Poucher, Sandra; Copeland, Rick (University Press of Florida, 2006)
Sandra Poucher and Rick Copeland have created this comprehensive karst glossary to correct discrepancies in communications among geologists and biologists, hydrologists and divers, cavers and speleologists, thereby enabling researchers to speak a common language.